Safeguarding Participants: Using Pseudonyms for Ensuring Confidentiality and Anonymity in Qualitative Research - Subedi, Khim Raj (KMC Journal, 2025)
Using pseudonyms for research participants is not new. However, there is little discussion in the Nepali context concerning the practical strategies for assigning pseudonyms. This study unfolds the multiple aspects of using pseudonyms in qualitative research and provides practical guidelines for novice researchers. Using narrative interviews and document analysis methods, this study integrates these approaches with critical reflections on PhD fieldwork. I argue that using pseudonyms for research participants is not straightforward and linear; instead, it is situational and depends on the research context, data sensitivity and participants’ desires. Hence, a researcher needs to be allowed to decide whether to use pseudonyms and which pseudonyms best safeguard their participants. The study’s findings show that ensuring absolute confidentiality and anonymity is challenging. However, a researcher’s careful and responsive approach helps protect participants’ privacy. While it is the autonomy of the researcher to use a proper strategy in assigning pseudonyms, negotiating with participants based on discussion with them could be a flexible alternative. Nepali researchers use an alphabet, alphabet and number together, alphabet and word together, and word phrase in disguising participants based on age, gender, ethnicity, culture and contemporary society. This study suggests including the process of assigning participants’ pseudonyms in research reports and publications.